Socio-ecological influences of leisure-time physical activity among Nepalese adults: a qualitative study - Susan Paudel; Alice J. Owen; Ben J. Smith (BMC, 2021)
Abstract Background With economic and social changes, participation in occupational and transport-related physical activity is declining among Nepalese adults, highlighting the growing importance of leisure-time physical activity. However, limited information is available to guide public health policies and interventions to promote leisure-time physical activity in Nepal. This study aimed to qualitatively explore the socioecological influences of participation in leisure-time physical activity among Nepalese adults aged 40 years and above. Methods A total of 51 adults (30 females and 21 males) participated in one of the nine focus groups conducted in Kathmandu, Nepal. A semi-structured guide based on the social-ecological model of physical activity was used to facilitate these focus groups. Data were analysed using a reflexive thematic analysis approach in NVivo 12. Results Participation in leisure-time physical activity was minimal and leisure time was mostly spent resting, socialising, or engaging in sedentary activities such as watching television. Walking was the most common form of leisure-time physical activity, and men reported being more active than women. Individual-level barriers included lack of knowledge, lack of skill, lack of motivation, considering oneself as sufficiently active and engagement in sedentary screen activities. Family and household responsibilities, lack of support and fear of being judged constituted the interpersonal barriers while environmental barriers included an absence of a supportive social norm, lack of open spaces, weather conditions and perceived lack of safety. Health benefits, prioritising physical activity, social support, provision of group-based activities and age-appropriate public exercise facilities were identified as major facilitators. Conclusion Critical issues that need to be addressed to increase leisure-time physical activity among Nepalese adults include traditional gender roles, family and social support, and social norms. Modifications of the built environment, such as public exercise facilities, offer further opportunities and will require coordination beyond the health sector.